TO ASSESS THE STATUS OF BACTERIA'S ANTIBIOTIC RESISTANCE OF BACTEREMIA IN NGHE AN OBSTETRICS AND GYNECOLOGY HOSPITAL IN 2021 (Vietnam Journal of Community Medicine, 2022)
Conduct cross-sectional descriptive study of blood culture samples to determine the rate of positive blood cultures in the period from 01.01.2021 to 30.09.2021 in the Department of hematology and microbiology, Nghe An Obstetrics and Children's Hospital. The satisfactory samples was conducted positive isolated strains of bacteria identification and antimicrobial susceptibility testing on the machine automatically or method Kirby - Bauer. Research criteria include: positive sample; time of appearance of positivity; gram-negative bacteria; gram positive; antibiotic resistance levels; assessment of antibiotic susceptibility (CLSI 2021) [8]. Rate of positive blood culture: 3.86%; intestinal bacteria 85.42%, Acinetobacter accounted for 4.17%, Pseudomonas aeruginosa 2.08%; other gram-negative bacteria (8. 33%). Antibiotic resistance of some isolates include E.coli, K.pneumoniae, E.cloacae, S.aureus, S.agalactiae.
Keywords: Bacteria, bacteremia, antibiotic resistance.